2018
DOI: 10.2174/1381612823666171019164220
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxypropyl-β-cyclodextrins and the Blood-Brain Barrier: Considerations for Niemann-Pick Disease Type C1

Abstract: The rare, chronic, autosomal-recessive lysosomal storage disease Niemann-Pick disease type C1 (NPC1) is characterized by progressively debilitating and ultimately fatal neurological manifestations. There is an urgent need for disease-modifying therapies that address NPC1 neurological pathophysiology, and passage through the blood-brain barrier represents an important consideration for novel NPC1 drugs. Animal investigations of 2-hydroxypropyl-β-cyclodextrins (HPβCD) in NPC1 in mice demonstrated that HPβCD does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The addition of cyclodextrin to chitosan carriers has the potential to enhance the pharmacokinetics, pharmacodynamics, stability, and brain uptake of the formulation. Similar research reports indicated the aforementioned properties when cyclodextrin are employed in drug delivery systems [108,109].…”
Section: Emulsionssupporting
confidence: 73%
“…The addition of cyclodextrin to chitosan carriers has the potential to enhance the pharmacokinetics, pharmacodynamics, stability, and brain uptake of the formulation. Similar research reports indicated the aforementioned properties when cyclodextrin are employed in drug delivery systems [108,109].…”
Section: Emulsionssupporting
confidence: 73%
“…HPβCD is more effective in reversing NPC symptoms in the NPC1 KO mice when delivered directly to the brain because HPβCD does not effectively cross the blood-brain barrier (BBB) [ 6 ]. For example, a 23 mg/kg HPβCD intracerebroventricular injection has a better outcome than a 4000 mg/kg HPβCD subcutaneous injection [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the principal difficulty of treatment with CD is the molecule’s inability to cross the blood–brain barrier, and while subcutaneous injection can decrease the level of cholesterol in several tissues, an intrathecal injection is needed to have any effect in the brain [ 48 , 49 ]. Indeed, intrathecal injections prevent some adverse effect of CD treatment such as lung toxicity.…”
Section: Cyclodextrins As Active Drugsmentioning
confidence: 99%